Byzantium in the Czech Lands (4th–16th centuries) : Historical and Art Historical Perspectives - Balcárek, Petr, 1965- (East Central and Eastern Europe in the Middle Ages, 450-1450 ;, 2023)
This book offers the first comprehensive study of Byzantine influence on the art and iconography of East Central Europe. Petr Balcárek focuses on the Byzantine cultural and religious legacy in the Czech lands, thereby bringing to light rarely seen images and presenting fresh hypotheses based on newly-explored theological interpretations and historical evidence. Including a discussion of the Czech and Slovak historiography on Byzantine studies, the work analyses significant artistic and iconographical artefacts in light of the intricate historical and political relationships that shaped Byzantine presence in these territories, comparing them with similar objects from other areas of Byzantine influence in order to draw wide-reaching conclusions.